2018
DOI: 10.1364/oe.26.019583
|View full text |Cite
|
Sign up to set email alerts
|

Quantum metrology beyond Heisenberg limit with entangled matter wave solitons

Abstract: Considering matter wave bright solitons from weakly coupled Bose-Einstein condensates trapped in a double-well potential, we study the formation of macroscopic non-classical states, including Schrödinger-cat superposition state and maximally path entangled N00N-state. We examine these macroscopic states by Mach-Zehnder interferometer in the context of parity measurements, which has been done to obtain Heisenberg limit accuracy for linear phase shift measurement. We reveal that the ratio of two-body scattering … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 80 publications
1
29
0
Order By: Relevance
“…3.1. Quantum field approach From the practical point of view it is more convenient to consider an interferometer consisting of two-mode condensate trapped in a double-well potential [23]. The Hamiltonian of the system under consideration is…”
Section: Quantum Model Of Coupled Matter-wave Solitonsmentioning
confidence: 99%
See 3 more Smart Citations
“…3.1. Quantum field approach From the practical point of view it is more convenient to consider an interferometer consisting of two-mode condensate trapped in a double-well potential [23]. The Hamiltonian of the system under consideration is…”
Section: Quantum Model Of Coupled Matter-wave Solitonsmentioning
confidence: 99%
“…Schrödinger picture is more suitable for the analysis of the system described by (18). Further we restrict ourselves by the Hartree approach justified in a large particle number limit [23]. The N-particle ground state vector, N Yñ | , can be written in this case as a product of N single-particle states…”
Section: Quantum Model Of Coupled Matter-wave Solitonsmentioning
confidence: 99%
See 2 more Smart Citations
“…[31,32] Furthermore, it was shown that matter wave bright solitons can form entangled states. [33] The addition of the dissipative terms allows one to control the velocity of a soliton such that it approaches zero. One of the key ingredients of our formulation is the particular form of the perturbative term which maintains the amplitude of the solution such that it does not decay to zero.…”
Section: Introductionmentioning
confidence: 99%